Design of a PLN Distribution Transformer Monitoring Tool Using Arduino and an Internet-Based MLX90614 Sensor - Hasnita, Ulfa; Atsauri, Muhammad Riki (Cattleya Darmaya Fortuna, 2023)
In this century's increasingly rapid technological advances, there is a great need for electronic component systems that are practical, efficient, and economical. One of them is measuring temperature. For this reason, it is necessary to have a temperature monitoring tool for the PLN distribution transformer using an Arduino with an MLX90614 sensor and connecting and displaying it on the internet. This system uses a microcontroller to calculate data from the sensors used. The MLX90614 sensor module is read by the microcontroller and serially connected to the GSM SIM800L module to send the data to the server so that the data can be accessed using the Web. The results of the overall system calculation can be sent to a computer or smartphone by accessing the specified website to view the data that has been presented in tabular form at time intervals determined by the user.